1998
DOI: 10.1295/polymj.30.981
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Permeation and Diffusion Properties of Semicrystalline Poly(4-methyl pentene-1) Membranes

Abstract: ABSTRACT:C02 permeation and diffusion behaviors ofpoly(4-methyl pentene-1) (PMP) with three different degrees of crystallinity were examined at -I 0 to 45°C. Permeation and diffusion coefficients in crystalline and amorphous parts of PMP were obtained by an extrapolation to 100 and 0% degrees of crystallinity, respectively. The inflection corresponding to the glass transition temperature of PMP was observed in Arrhenius plot of both the permeability and diffusion coefficients only for the amorphous part of PMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…The obtained dependences are difficult to interpret as a linear with a flex-point in the T g region. These temperature diffusion data are in contrary with permeability data for CO 2 in PMP [45]. In whole, PMP can be considered as a two phase polymer with ρ a ~ ρ c at T ~T g .…”
Section: Resultscontrasting
confidence: 62%
“…The obtained dependences are difficult to interpret as a linear with a flex-point in the T g region. These temperature diffusion data are in contrary with permeability data for CO 2 in PMP [45]. In whole, PMP can be considered as a two phase polymer with ρ a ~ ρ c at T ~T g .…”
Section: Resultscontrasting
confidence: 62%
“…Gaps of 4 Å between the chain segments were predicted in the crystalline structure of this polymer in agreement with low crystalline density 4. Gas‐transport measurements have revealed that small gas molecules such as carbon dioxide and methane can dissolve and permeate in this crystalline structure to an extent that is significant in comparison with the amorphous phase 5, 6. Recently, a different semicrystalline polymer, with potentially similar properties, attracted our attention.…”
Section: Introductionsupporting
confidence: 56%
“…The PMP is commercial one, and contains more than 95% of isotactic triads determined by 13 C NMR spectroscopy. Six kinds of membranes with different crystallinities were prepared by appropriate treatments.…”
Section: Sample Preparationsmentioning
confidence: 99%
“…This finding is probably attributed to an increase in tortuous diffusion path. 10,13 In the cylindrical cavity formed in PMP crystal, a gas molecule diffuses restrict- edly along molecular chains of PMP. Because the PMP crystal in the membranes studied here should orientate randomly, tortuous diffusion path of a gas molecule increases with increasing crystallinity.…”
Section: Xe Nmr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation